2008
DOI: 10.1038/cgt.2008.26
|View full text |Cite
|
Sign up to set email alerts
|

Radiation improves gene delivery by a novel transferrin-lipoplex nanoparticle selectively in cancer cells

Abstract: Selective gene transfer to tumor is critical in cancer gene therapy. We previously used ionizing radiation to improve adenovirus uptake in intrahepatic tumors but liver cytotoxicity associated with the viral administration still occurred. Here, we explore the potential of radiation for improving gene delivery by a virus-mimicking nanoparticle, transferrin (Tf)-cationic liposome-DNA complex (Tf-lipoplex). Transduction by Tf-lipoplex was highly efficient in various cell lines and further increased by radiation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The present data clearly show that urea, and possibly other chemical penetration enhancers, are able to increase liposomal AsODN delivery and its antitumoral effect both in vivo and in vitro . In comparison with other enhancement methods, such as sonophoresis , electroporation, complex formation or radiation , which are reported for the enhancement of liposomal or nonliposomal ODN delivery, chemical penetration enhancers are considered to be less invasive, readily available, easy to apply and less expensive. This strategy may open a new era in the field of liposomal gene delivery to cancer cells (especially at subcellular levels).…”
Section: Discussionmentioning
confidence: 99%
“…The present data clearly show that urea, and possibly other chemical penetration enhancers, are able to increase liposomal AsODN delivery and its antitumoral effect both in vivo and in vitro . In comparison with other enhancement methods, such as sonophoresis , electroporation, complex formation or radiation , which are reported for the enhancement of liposomal or nonliposomal ODN delivery, chemical penetration enhancers are considered to be less invasive, readily available, easy to apply and less expensive. This strategy may open a new era in the field of liposomal gene delivery to cancer cells (especially at subcellular levels).…”
Section: Discussionmentioning
confidence: 99%
“…Non-viral gene delivery remains an active area of research with the main focus being improvement of delivery and transfection efficiency. Recently, Abela et al reported the preparation of a virus-mimicking nanoparticle, transferrin (Tf)-cationic liposome-DNA complex (Tf-lipoplex) by encapsulating plasmid DNA cytomegalovirus-green fluorescent protein (CMV-GFP) inside the core of liposomes 53. They reported that Tf-lipoplex achieved high gene delivery efficacy in C57BL mice carrying subcutaneous LLC1 tumor xenografts.…”
Section: Multifunctional Nanomedicinementioning
confidence: 99%
“…Addition of the transferrin (Tf) ligand to a cationic liposome complex resulted in significantly increased in vitro and in vivo transfection efficiency in squamous cell carcinoma of the head and neck (SCCHN, 70-80% transfection rate compared with only 5–20% by liposome alone). Both p53 gene and siRNAs have been successfully delivered to the target organs using TfR conjugated liposomes or nanoparticles in treating many types of cancers including pancreatic cancer [9, 73-76]. …”
Section: Potential Targets For Specific Deliverymentioning
confidence: 99%